A new species of the genus Orchesia Latreille (Coleoptera: Melandryidae) from Baltic amber with a key to species described from fossil resins - Alekseev, Vitalii I.; Bukejs, Andris (Zootaxa, 2015)
Orchesia (Orchestera) canaliculata sp. nov. is described and illustrated from Eocene Baltic amber (Kaliningrad Region, Russia). New fossil records on O. turkini Alekseev & Bukejs and O. rasnitzyni Nikitsky are presented. A key to species of Orchesia Latreille, described from fossil resins, is provided.